Variable search intensity in an economy with coordination unemployment - Leo Kaas (Institute for the Study of Labor (IZA), 2008)
This paper analyzes an urn-ball matching model in which workers decide how intensively they sample job openings and apply at a stochastic number of suitable vacancies. Equilibrium is not constrained efficient; entry is excessive and search intensity can be too high or too low. Moreover, an inefficient discouraged-worker effect among homogenous workers emerges under adverse labor market conditions. Unlike existing coordination-friction economies with fixed search intensity, the model can account for the empirical relation between the job-finding rate and the vacancy-unemployment ratio, provided that search costs are small and that search intensity is sufficiently procyclical.
urn:nbn:de:101:1-20081014486
Keywords: E24; 330; Matching function; coordination frictions; unemployment; Arbeitslosigkeit; Arbeitsmarktungleichgewicht; Arbeitsuche; Offene Stellen; Matching; Koordination; Wohlfahrtseffekt; Theorie